Period-Two Trichotomies of a Difference Equation of Order Higher Than Two - Burgić, Dževad; Kalabuˇsić, S.; Kulenović, M. R. S. (Sarajevo Journal of Mathematics, 2024)
We investigate the period-two trichotomies of solutions of the equation x_n+1 = f(x_n, x_n-1,x_n-2), n=0, 1, … where the function f satisfies certain monotonicity conditions. We give fairly general conditions for period-two trichotomies to occur and illustrate the results with numerous examples. 1991 Mathematics Subject Classification. 39A10, 39A11